PENGARUH PENGGUNAAN MEDIA ANDROID TERHADAP KEMAMPUAN FOKUS ANAK BERKEBUTUHAN KHUSUS - Yatim Riyanto; Andi Mariono; Abidin Arridho Ajitama (Akademika : Jurnal Teknologi Pendidikan, 2023)
Children with special needs often struggle to maintain their focus. This study aims to evaluate the influence of using Android media on the focus ability of children with special needs. The research was conducted with 10 special needs children at a Cerebral Palsy Care Foundation. The research method employed was quasi-experimental with a single-group pre-test post-test control design. The results of the study indicate that the use of Android media significantly improves the focus ability of children with special needs. The pre-test data showed an average score of 2.9, while the post-test data showed an average score of 10. The Sign Test was used to calculate the results, and the ZH value (5.06) was found to be greater than the 5% Z-table value (1.64) / ZH (5.06) > Z table (1.64). Therefore, it is recommended to consider using Android media as an alternative to enhance the focus ability of children with special needs.